Pengembangan Kawasan Pertanian Di Kabupaten Sigi Provinsi Sulawesi Tengah - Wildani Pingkan Suripurna Hamzens (Jurusan Teknik Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 94118 e-mail :Jurusan Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 941, 2011)
Regional District of Central Sulawesi Province Sigi is a potential agricultural areas (food crops, horticulture, plantation, forestry, animal husbandry, and fisheries). This paper aims to reveal the efforts that need to be done for the Development of Agricultural Regions in Sigi District, which includes: (1) spatial structure including infrastructure and facilities, (2) Type of Activity, (3) Community Involvement, and (4) Environmental Sustainability.